2010
DOI: 10.1152/ajpheart.00741.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin encapsulation in vesicles retards NO and CO binding and O2release when perfused through narrow gas-permeable tubes

Abstract: Sakai H, Okuda N, Sato A, Yamaue T, Takeoka S, Tsuchida E. Hemoglobin encapsulation in vesicles retards NO and CO binding and O2 release when perfused through narrow gas-permeable tubes. Am J Physiol Heart Circ Physiol 298: H956 -H965, 2010. First published December 31, 2009 doi:10.1152/ajpheart.00741.2009.-Intravenous administration of cell-free Hb induces vasoconstriction and circulatory disorders, presumably because of the intrinsic affinities to endogenous nitric oxide (NO) and carbon monoxide (CO) as vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
3
7
1
Order By: Relevance
“…The k off , O2 values for acellular Hbs are comparable to most of the other studies reported in the literature (Table 1). However, Tuschida and coworkers 46 have reported higher values of k off , O2 for the Hb used in their study (84.00 s −1 ) as compared to values in the literature (≈40.00 s −1 ). 47 This higher value could be due to the use of organic solvents during the Hb purification process or heat pasteurization of the Hb used in their studies, which may have chemically modified the Hb and resulted in an increase in k off , O2 .…”
Section: Resultscontrasting
confidence: 60%
“…The k off , O2 values for acellular Hbs are comparable to most of the other studies reported in the literature (Table 1). However, Tuschida and coworkers 46 have reported higher values of k off , O2 for the Hb used in their study (84.00 s −1 ) as compared to values in the literature (≈40.00 s −1 ). 47 This higher value could be due to the use of organic solvents during the Hb purification process or heat pasteurization of the Hb used in their studies, which may have chemically modified the Hb and resulted in an increase in k off , O2 .…”
Section: Resultscontrasting
confidence: 60%
“…Moreover, significant retardation in O 2 offloading has been observed in RBCs when compared with acellular Hb (2–17 s −1 compared with 36–43 s −1 ) 28, 40, 41. In addition, PEG‐LEH dispersions had significantly lower k off , O2 ( P < 0.05) compared with other acellular HBOCs (17–23 s −1 compared with 22–130 s −1 ) 42–46. All these results suggest that encapsulation of Hb in a membrane bound particle similar to that of a RBC, plays a critical role in regulating the delivery of O 2 .…”
Section: Resultsmentioning
confidence: 82%
“…Safety and efficacy evaluations of its use, mainly using rodents, as a resuscitative fluid for hemorrhagic shock are conducted energetically, 7,8 as a priming fluid for extracorporeal membrane oxygenator, 9 and as a targeted oxygen carrier for ischemic tissues [10][11][12] and tumors. 13 Actually, Hb encapsulation shields the toxic effects of stroma-free Hbs, especially preventing unwanted reactions of Hb with endogenously produced NO, 14,15 thereby preventing NO-related vasoconstriction and hypertension. 16 However, it is important to confirm the biocompatibility of ''vesicles.''…”
Section: Introductionmentioning
confidence: 99%